Nowa umowa kapitałowa (NUK) w polskich bankach MSSF - Ostojski, Wojciech (The New Capital Accord (NCA) in Polish Banks and IASC, 2007)
The article presents New Capital Accord (NCA) in the Polish financial institutions (banks). The author describes new solutions in three levels and their relations to the IASC.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 137-151